Constitucionalização de políticas públicas e emendamento constitucional no Brasil - Lima, Giovanna de Moura Rocha (2016)
This Thesis investigates the constitutionalization of public policies and what has been its amendment pattern in post-1988 Brazil. We offer a criteria for selecting relevant proposed amendments to the Constitution in the Brazilian case and evaluate which topics of public policy were constitutionalized, which are more present in the Proposed Amendments and Constitutional Amendments in the country, and if those distribuitions relate to each other. In particular, the objective of this Thesis is to evaluate the different patterns of constitutionalization and amendment of different issues of public policy. The research covers the submission and aproval period from 1988-2010 for the Proposals in the Brazilian Chamber of Deputies.